ANALISIS FAKTOR PENGHAMBAT KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS 1 SD IP SALSABILA AL IKHSAN - Amalia, Ummu Azka; Kusumawati, Erna Risfaula (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study describes and analyzes the factors inhibiting initial reading difficulties in students. The research subject of grade 1 students of SDIP Salsabila Magelang. The purpose of the study is to find out and be able to analyze the factors of difficulty in the beginning of reading experienced by students. Due to the results in reading the beginning of each learning process students have difficulty reading words with more than three or more syllables. This research uses descriptive qualitative research methods by previously conducting interviews. From the results of the study, it was found that students had difficulty understanding words with vowels which made the lack of memory of letters.